Perencanaan Instalasi Air Conditioner (AC) Pada Hotel Champions - Yudi Chandra (Indonesian Society of Applied Science, 2021)
Comfort in a room is a necessity for everyone who is in the room, to support the activity in the room and increase work productivity, Air Conditioner is an equipment used to condition the air in a room so that it can reach temperature and humidity according to the conditions air that provides work comfort for people who do certain activities in the room. Therefore, the air conditioning system or air conditioning system (AC) has become a necessity in buildings, offices and housing, all of which can not be separated from the need for electrical energy, especially for air conditioner installations. To get air with the desired conditions, the selected equipment must match the capacity according to the cooling load in the room, for this final project special installation planning for Air Conditioners is done, namely calculations to determine the cooling load according to the room, as well as conductor selection in accordance with the calculation load, from the calculation results, obtained the number of air-cooled loads or first-floor Champion hotel air conditioner is 108,692 BTU / day with a total power of 7,920 watts, and the appropriate cross section based on the count is 1.5 mm2, and the main safety (MCCB) is 25 A.